1997
DOI: 10.1097/00007890-199704150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Pretransplant Blood Transfusions in Cadaver Kidney Recipients

Abstract: Within a collaborative project of 14 transplant centers, prospective recipients of cadaver kidney grafts were randomized to receive either three pretransplant transfusions or transplants without transfusions. RESULTS; The graft survival rate was significantly higher in the 205 transfusion recipients than in the 218 patients who did not receive transfusions (at 1 year: 90+/-2% vs. 82+/-3%, P=0.020; at 5 years: 79+/-3% vs. 70+/-4%, P=0.025). Cox regression analysis showed that this effect was independent of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
1
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(115 citation statements)
references
References 10 publications
6
102
1
6
Order By: Relevance
“…Proposed mechanisms for this immunosuppressive effect include the induction of suppressor T cells and antiidiotypic antibodies, deletion of naive T cells, and decreased natural killer cell activity. [23][24][25][26][27][28][29] Previous investigators have observed that, in adult populations that have undergone cardiovascular or colorectal surgery, the risk of surgical site infection increases 7%-14% with each unit of packed red blood cells transfused. [23][24][25][26][27][28][29] Transfusion may also be a marker for frequent access of arterial catheters and CVCs.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms for this immunosuppressive effect include the induction of suppressor T cells and antiidiotypic antibodies, deletion of naive T cells, and decreased natural killer cell activity. [23][24][25][26][27][28][29] Previous investigators have observed that, in adult populations that have undergone cardiovascular or colorectal surgery, the risk of surgical site infection increases 7%-14% with each unit of packed red blood cells transfused. [23][24][25][26][27][28][29] Transfusion may also be a marker for frequent access of arterial catheters and CVCs.…”
Section: Discussionmentioning
confidence: 99%
“…To re-examine the transfusion effect, Opelz et al performed the first randomized clinical trial of pretransplant blood transfusions on graft outcomes. A total of 423 prospective cadaveric kidney transplant recipients from 14 European centers were randomly assigned to receive three pretransplant packed cell transfusions (n=205) or transplants without transfusions (n=218) (19). The graft survival rate was significantly higher in the transfusion recipients than in patients who did not receive transfusions (at 1 year: 90%62% versus 82%63%, P=0.02; at 5 years: 79%63% versus 70%64%, P=0.03).…”
Section: Overview Of Blood Transfusion Use In Patients With Ckdmentioning
confidence: 99%
“…Allogeneic blood transfusion has been demonstrated to promote tumour growth in experimental animals. 8,9 Renal allograft survival was better in patients receiving allogeneic blood transfusion prior to transplant 3,10 which is consistent with a reduction in immune function. The risk of recurrent cancer has not been demonstrated in randomized control trials.…”
mentioning
confidence: 80%
“…Il y a une perte concomitante de globules rouges de 4 à 19 % associée à la filtra-tion. 2,3 Pendant la conservation, les globules blancs produisent des cytokines, lesquelles sont impliquées dans la communication intracellulaire et influencent le développement et le maintien de l'immunité et du processus inflammatoire. Théoriquement, ces cytokines peuvent nuire à la fonction immunitaire, 4-7 la réduction leucocytaire préconservation pourrait donc être supérieure à celle de la postconservation, quoique les essais cliniques n'aient pas confirmé cette hypothèse.…”
unclassified